Chiral plasmonics and enhanced chiral light-matter interactions - Du, Wei (2020)
Chirality, which describes the broken mirror symmetry in geometric structures, exists macroscopically in our daily life as well as microscopically down to molecular levels. Correspondingly, chiral molecules interact differently with circularly polarized light exhibiting opposite handedness (left-handed and right-handed). However, the interaction between chiral molecules and chiral light is very weak. In contrast, artificial chiral plasmonic structures can generate “super-chiral” plasmonic near-field, leading to enhanced chiral light-matter (or chiroptical) interactions. The “super-chiral” near-field presents different amplitude and phase under opposite handedness incidence, which can be utilized to engineer linear and nonlinear chiroptical interactions. Specifically, in the interaction between quantum emitters and chiral plasmonic structures, the chiral hot spots can favour the emission with a specific handedness. This article reviews the state-of-the-art research on the design, fabrication and chiroptical response of different chiral plasmonic nanostructures or metasurfaces. This review also discusses enhanced chiral light-matter interactions that are essential for applications like chirality sensing, chiral selective light emitting and harvesting. In the final part, the review ends with a perspective on future directions of chiral plasmonics.